2015
DOI: 10.1039/c4sm02675f
|View full text |Cite
|
Sign up to set email alerts
|

Molecular architecture requirements for polymer-grafted lignin superplasticizers

Abstract: Superplasticizers are a class of anionic polymer dispersants used to inhibit aggregation in hydraulic cement, lowering the yield stress of cement pastes to improve workability and reduce water requirements. The plant-derived biopolymer lignin is commonly used as a low-cost/low-performance plasticizer, but attempts to improve its effects on cement rheology through copolymerization with synthetic monomers have not led to significant improvements. Here we demonstrate that kraft lignin can form the basis for high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 50 publications
0
19
0
2
Order By: Relevance
“…The changes in molecular structure of Pl provide the improvement of their plasticising efficiency. Nowadays, there are a significant number of research works on the synthesis of Pl with new molecular architecture, which contributes to the changes in rheological and technological properties of cement-based materials [43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…The changes in molecular structure of Pl provide the improvement of their plasticising efficiency. Nowadays, there are a significant number of research works on the synthesis of Pl with new molecular architecture, which contributes to the changes in rheological and technological properties of cement-based materials [43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…Superplasticizers are a class of high‐performance anionic polymers that is designed to modify rheological properties of hydraulic cement . Gupta et al demonstrated high‐performance dispersants obtained through a grafted architecture using RAFT polymerization of polyacrylamide from a lignin macroinitiator [Scheme (b)] . Significant reductions in yield stress were observed in ordinary portland cement when it used with the prepared lignin‐graft‐polyacylamide.…”
Section: Graft‐from Methodsmentioning
confidence: 57%
“…(a) Graft‐from RAFT polymerization of acrylic acid and acrylamide . (b) Graft‐from RAFT polymerization of acrylamide . (c) Graft‐from RAFT polymerization of soybean oil‐derived monomers .…”
Section: Graft‐from Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Gra, star, or branch copolymers are also possible with RAFT polymerization. [29][30][31][32][33][34][35][36][37][38][39] Shan et al 40 used a multi-arm star RAFT chain transfer agent (CTA) to synthesize star PAM copolymers. A similar approach was used for preparation of hyperbranched copolymers with AM and acrylonitrile.…”
Section: Introductionmentioning
confidence: 99%